SELF-ESTEEM, FORGIVENESS DAN SUBJECTIVE WELL BEING PADA WANITA DEWASA MUDA YANG MENGALAMI PERCERAIAN - Putri, Shanti Asih Karina; Wahyu Rahardjo (Bajang Institute, 2024)
This study aims to determine the description of subjective well-being (SWB) in young adult women who are divorced. Subjective well-being (SWB) is a picture of happiness, life satisfaction, and a picture of individual positive-negative affect. Self-esteem (self-respect) and forgiveness (forgiveness) are the basis for an individual's positive assessment of himself. Therefore, this study was conducted to determine the relationship between self-esteem, forgiveness and SWB in young adult women who experience divorce. Participants in this study were 100 people. This study uses three measuring tools, namely the Rosenberg Self-Esteem Scale (RSES), the Heartland Forgiveness Scale (HFS), and the Oxford Happiness Questionnaire (OHQ). This study also wants to see how big the role of self-esteem and forgiveness for SWB in young adult women who experience divorce. This research is a quantitative research with non-probability sampling technique. The result of this research is that there is a significant influence between self-esteem and forgiveness on subjective well-being